(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The educational status of children with disability and the level of educational attainments of differently abled persons have been examined for the rural-urban areas, gender, age groups and social group wise across the states and NSSO regions by types of disability. The vast majority of differently abled young persons have been excluded from most educational, economic, social and cultural opportunities. Literacy among persons with disabilities was found to be considerably lower in comparison with the rest of the population. The case of women with disabilities is noteworthy as their literacy rates are more likely found to be lower than even their male counterparts on account of double discrimination that they suffer, on the grounds of both gender and impairment. The differently abled persons are more likely found to be out of job and families with a differently abled member are often worse off than the families with a nondifferently abled member. This leads to lower employment and incomes